(untitled) (The Pakistan Development Review, 2006)
Decentralisation is associated with the hope that “bringing government closer to the people” will improve the provision of public services by increasing people’s voice in decision-making, and by making the government more accountable to them. Decentralisation is also associated with the hope that disadvantaged groups of society, including the poor and women, will have better possibilities to exercise voice at the local level. Some countries have combined decentralisation with affirmative action, for example, by reserving seats in local councils for women and other disadvantaged groups. Yet the empirical evidence regarding the impacts of decentralisation has been mixed [Bardhan (2002); von Braun and Grote (2002); Jütting, et al. (2004); Steiner (2005)]. In many cases, political decentralisation has not been associated with fiscal and administrative decentralisation, thus limiting the scope of what local governments can actually do. Building capacity at the local level and overcoming coordination problems has been another challenge. Local elite capture has been identified as a major problem that can prevent positive effects of decentralisation for the poor, especially in societies with hierarchical power structures at the local level [Bardhan (2002)]. With regard to gender, there are concerns that decentralisation—even if associated with affirmative action—will not be sufficient to overcome gender-based discrimination. Again, the empirical evidence is mixed [ADB (2004)]. Chatthobadhay and Duflo (2004) found that that women who were elected as village leaders under the reservation policy in the Indian states of West Bengal and Rajastan invested more in those public goods that more closely linked to women’s concerns, such as drinking water. Baden (1999) showed that it depends on local power structures and on the availability and competition over resources whether or not women benefit from decentralisation. In view of the mixed results, important knowledge gaps remain regarding the possibilities to promote public service provision for the poor and for women through political decentralisation and associated affirmative action.